Associative effect of tannins and monensin as manipulators of rumen fermentation on the mitigation of methane production in cattle - Tseu, Ramos Jorge (2019)
Climate changes and global warming are topics of scientific debate. The increase of greenhouse gases has been pointed out as one of the main causes of the changes. The study aimed to evaluate the associative effect of monensin (M) with different levels of tannins (T) on feeding, digestive and rumen fermentation (ex-situ technique) parameters as well as on anaerobic biodigestion of waste. In a 2 x 4 factorial arrangement, 8 cannulated Nellore cows were distributed in 2 contemporary 4 x 4 Latin squares and received 8 experimental diets which differed in the level of inclusion of T of A. mearnsii extract (0.0, 0.75, 1.5, and 2.25% DM) and M which was daily administered to each cow (about 32 mg/kg DM) of one square. To evaluate the production of biogas, experimental batch-type anaerobic biodigesters were used in a completely randomized design. The data were analyzed by the Statistical Analysis System (SAS 9.3, Institute Inc., 2013). The results have shown little interaction between M and T. Regarding the feeding, digestive and N balance parameters, the T linearly reduced DM and water intake, the total apparent digestibility of DM, CP, TDN and OM; for the NDF and ADF the reduction was quadratic. The T linearly reduced rumen disappearance rate by linearly reduce both passage and digestion rates. T also linearly reduced urinary urea excretion, but both additives had no effect on the synthesis and efficiency of microbial protein synthesis. M reduced the proportion of N excreted in feces, but had no effect on N balance, whereas T linearly increased fecal N and linearly reduced urinary and retained N. Regarding the parameters of rumen fermentation, no significant effect of M was observed on CH4 production, but on the reduction of acetate:propionate ratio. T linearly reduced the production of CH4 and total SCFA. Regarding anaerobic biodigestion, M and T reduced the nutrient removal efficiency. M and T had independent effects on rumen metabolism, however, the use of T of A. mearnsii extract up to 2.25% DM is a safe option for cattle, with potential to mitigate rumen CH4. The combined use of M and T reduced the potential of biogas production by reducing the nutrient use efficiency. M inhibited the effect of T on the reduction of nutrient use efficiency of the waste through antagonistic interaction.